Circadian rhythm disruption results in visual dysfunction. Issue 6 (7th February 2022) - Mathew, Deepa; Luo, Qianyi; Bhatwadekar, Ashay D.
Abstract: Artificial light has been increasingly in use for the past 70 years. The aberrant light exposure and round‐the‐clock nature of work lead to the disruption of biological clock. Circadian rhythm disruption (CRD) contributes to multiple metabolic and neurodegenerative diseases. However, its effect on vision is not understood. Moreover, the mammalian retina possesses an autonomous clock that could be reset with light exposure. We evaluated the impact of CRD on retinal morphology, physiology, and vision after housing mice in a disruption inducing shorter light/dark cycle (L10:D10). Interestingly, the mice under L10:D10 exhibited three different entrainment behaviors; "entrained, " "free‐running, " and "zigzagging." These behavior groups under CRD exhibited reduced visual acuity, retinal thinning, and a decrease in the number of photoreceptors. Intriguingly, the electroretinogram response was decreased only in the mice exhibiting "entrained" behavior. The retinal proteome showed distinct changes with each entrainment behavior, and there was a dysfunctional oxidative stress‐antioxidant mechanism. These results demonstrate that CRD alters entrainment behavior and leads to visual dysfunction in mice. Our studies uniquely show the effect of entrainment behavior on retinal physiology. Our data have broader implications in understanding and mitigating the impact of CRD on vision and its potential role in the etiology of retinal diseases.